The Influence of Accounting Information Systems and Cloud Computing on the Performance of Accounting Firms: A Moderating Effect Analysis (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to study the influence of Accounting Information Systems (AIS) and cloud computing on the performance of accounting firms, focusing on analyzing the moderating role of cloud computing. Data was collected from 120 accounting firms using questionnaires and analyzed through descriptive statistics including frequency, percentage, mean, and standard deviation, while structural equation modeling was used for hypothesis testing. The findings reveal that AIS components influencing operational performance in descending order are: security and integrity (β = 0.202), confidentiality and privacy (β = 0.119), and system availability (β = 0.088), while system quality showed no significant impact on performance. Cloud computing demonstrated the highest positive influence on performance (β = 0.386). Additionally, cloud computing was found to moderate the relationship between system availability and performance in an antagonistic direction, meaning as cloud computing levels increase, the influence of system availability on performance decreases. This research recommends that accounting firms prioritize developing systems with data security and integrity, and consider implementing cloud computing to enhance operational efficiency.